Rosuvastatin but not ezetimibe improves endothelial function in patients with heart failure, by mechanisms independent of lipid lowering. - Gounari, P; Tousoulis, D; Antoniades, C; Kampoli, A; Stougiannos, P; Papageorgiou, N; Roulia, G; Stefanadi, E; Siasos, G; Tsioufis, C; Stefanadis, C (2010)
INTRODUCTION: Congestive heart failure (HF) is characterised by increased proinflammatory stimulation and impaired endothelial function. Statin treatment exerts a beneficial effect on endothelial function and inflammatory process in patients with atherosclerosis. However, its effect in patients with HF is not well studied. Therefore, in the present study we compared the effect of short-term treatment with rosuvastatin or ezetimibe on endothelial function in patients with HF. METHODS: In this double-blind, placebo controlled, cross-over trial, 22 patients with HF were randomised to receive ezetimibe 20 mg/d or rosuvastatin 10 mg/d for 4 weeks, with 4 weeks wash-out period between the two interventions. Endothelial function was evaluated by flow mediated dilation (FMD) in the brachial artery at the beginning and at the end of each treatment period. RESULTS: There was no change in the baseline brachial diameter after treatment with either ezetimibe (p=NS) or rosuvastatin (p=NS). However, there was a significant improvement of FMD in the rosuvastatin group (p<0.05) but not in the ezetimibe group (p=NS). The changes in lipid levels were similar between groups (p=NS). The change in FMD was not significantly correlated with the decrease of serum LDL in either the ezetimibe or rosuvastatin treated groups. CONCLUSIONS: Rosuvastatin improves endothelial function in patients with congestive heart failure, by mechanisms independent of lipid-lowering. On the contrary, lipid-lowering treatment achieved by ezetimibe is unable to affect endothelial function in these patients. These findings indicate a direct beneficial effect of statins in patients with congestive heart failure, further to lipid-lowering.